Unveiling the Role of Rural Social Networks in Facilitating Rural-Urban Migration and the Survival of Self-Employed Youth in Iringa Municipality, Tanzania - Manyerere, David J. (Tanzania Journal for Population studies and Development, 2020)
Youth unemployment is a global challenge but more severe among developing countries such as Tanzania. In addressing the challenge, rural youth resort to migrating to urban areas in search of perceived vast economic opportunities. This paper explores how rural social networks facilitate youth rural-urban migration and migrants' survival in Iringa Municipality. It shows that cooperative values manifested in day to day socio-economic relations among village dwellers nurture long term social networks that are the potential to facilitate youth migration and their survival in urban areas. The paper unveils how earlier migrants support the newcomers to join them and access economic opportunities. They provide fare to travel, hosting assistance and connect them to urban income generation opportunities. As a survival strategy, youth migrants use their rural social relations to form economic groups to work together, exchange information about alternative sources of incomes as well as helping each other when faced with socio-economic crises. However, despite such accrued rural social networks benefits, some youth migrants fail to meet their expectations given urban life challenges as they earn insufficient income to cater for their basic needs. To avoid such urban vulnerability, the paper proposes some suggestions. Before migration, rural youth need to be informed to make proper decisions based on the correct information, and they should work hard while in the urban area to cope with a new working environment. Keywords: